RELATIONSHIP BETWEEN GLYCOCALYX COMPONENTS AND MICROALBUMINURIA IN PATIENTS WITH DIABETES MELLITUS - Shanza Rafi; Kamran Shauket; Shazia Naz; Zunairah Hamayun; Nasir Islam; Tayyaba Yasin; Hafsa Yasin; Filza Karim; Rizwana Dilshad (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Diabetes mellitus is a disease of deregulated blood glucose homeostasis. Microalbuminuria has been described as an early sign of kidney damage. The aim of the study was to determine the association of glycocalyx metabolites with microalbuminuria in type 1 diabetic patients. To determine the association of glycocalyx metabolites with microalbuminuria in diabetic patients. This cross-sectional study was recruited from the 90 patient’s department of Children's Hospital on the recommendation of a consultant endocrinologist. Patients were designated as having microalbuminuria if they had a 24-h urine measurement >30 mg or an albumin-to-creatinine ratio >30 mg/g albumin-to-creatinine. Total cholesterol, HDL cholesterol, and triglycerides were measured by standard enzymatic methods. Blood and urine samples were obtained from diabetic patients. A probability value of P